2015
DOI: 10.1007/s00395-015-0507-4
|View full text |Cite
|
Sign up to set email alerts
|

Septic cardiomyopathy in rat LPS-induced endotoxemia: relative contribution of cellular diastolic Ca2+ removal pathways, myofibrillar biomechanics properties and action of the cardiotonic drug levosimendan

Abstract: Cardiac dysfunction is a common complication in sepsis and is characterized by forward pump failure. Hallmarks of septic cardiomyopathy are decreased myofibrillar contractility and reduced Ca(2+) sensitivity but it is still not clear whether reduced pump efficiency is predominantly a diastolic impairment. Moreover, a comprehensive picture of upstream Ca(2+) handling mechanisms and downstream myosin biomechanical parameters is still missing. Ca(2+)-sensitizing agents in sepsis may be promising but mechanistic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…It has been demonstrated that when endotoxin like LPS binds the receptor TLR4 that is expressed on cardiomyocytes and macrophages, it initiates the activation of NF-κB and permits NF-κB translocating into nucleus [23]. After undergoing LPS insult, both the macrophages and cardiomyocytes can release a great quantity of inflammatory mediator, such as MCP-1, GM-CSF, IL-1α, IL-1β, IL-6, IL-7, IL-8, and IL-12 [22,23].These inflammatory cytokines could give rise to imbalance of calcium homeostasis [24], disturbance of energy metabolism [25], impairment of adrenergic signaling [26], and excess production of nitric oxide [27], all of which facilitate decreased contractility, diastolic dysfunction, impaired ejection fraction and reduced cardiac index. The high mobility group A1 (HMGA1) has a significant impact on the proliferation, differentiation, activation and recruitment of inflammatory cells, as well as the secretion of inflammatory mediators and cytokines [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that when endotoxin like LPS binds the receptor TLR4 that is expressed on cardiomyocytes and macrophages, it initiates the activation of NF-κB and permits NF-κB translocating into nucleus [23]. After undergoing LPS insult, both the macrophages and cardiomyocytes can release a great quantity of inflammatory mediator, such as MCP-1, GM-CSF, IL-1α, IL-1β, IL-6, IL-7, IL-8, and IL-12 [22,23].These inflammatory cytokines could give rise to imbalance of calcium homeostasis [24], disturbance of energy metabolism [25], impairment of adrenergic signaling [26], and excess production of nitric oxide [27], all of which facilitate decreased contractility, diastolic dysfunction, impaired ejection fraction and reduced cardiac index. The high mobility group A1 (HMGA1) has a significant impact on the proliferation, differentiation, activation and recruitment of inflammatory cells, as well as the secretion of inflammatory mediators and cytokines [28].…”
Section: Discussionmentioning
confidence: 99%
“…CLP increased myocardial angiotensin II content, which may be associated with the disturbance of Ca 2+ transport in the cardiac SR [ 79 ]. LPS also specifically impaired sarcolemmal diastolic Ca 2+ extrusion pathways by depressing the function of the Na + /Ca 2+ exchanger and the plasmalemmal Ca 2+ ATPase, which in turn resulted in intracellular diastolic Ca 2+ overload [ 80 ]. This disruption of cellular Ca 2+ homeostasis in cardiomyocytes may contribute to SIMD.…”
Section: Pathogenesis Of Simdmentioning
confidence: 99%
“…Similarly, the downstream cellular pathophysiology of myocardial depression is still obscure, although in experimental models, a number of contributing mechanisms have been reported. The cardiac cellular mechanisms include a reduction of L-type calcium current (I CaL ) ( Lew et al, 1996 ; Zhong et al, 1997 ; Stengl et al, 2010 ), altered calcium transients ( Ren et al, 2002 ), increased calcium leakage from the sarcoplasmic reticulum ( Zhu et al, 2005 ), impaired sarcolemmal diastolic calcium extrusion pathways ( Wagner et al, 2015 ), oxidation and subsequent activation of calcium and calmodulin-dependent protein kinase with phosphorylation of the ryanodine receptor ( Sepúlveda et al, 2017 ), altered phosphorylation and calcium sensitivity of cardiac myofibrillar proteins ( Wu et al, 2001 ), and/or mitochondrial dysfunction ( Levy et al, 2004 ; Watts et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%